Охотники за растениями - Рид Томас Майн (Книжное издательство, 1990)
Экземпляры: ф.2 (1990) / Инвентарный номер: 31851 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Р 49 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44